Effect of block composition on the morphology and transport properties of sulfonated fluoroblock copolymer blend membranes. Issue 11 (7th February 2017) - Guerrero‐Gutiérrez, Edward M.A.; Pérez‐Pérez, Maritza; Newbloom, Gregory M.; Pozzo, Lilo D.; Suleiman, David
Abstract : This study focuses on the relationship between the transport properties and the morphological changes of ionic block copolymer blend membranes, as a function of the fluoroblock chemical composition and loading. Poly(styrene‐b‐isobutylene‐b‐styrene) was sulfonated and blended with three different fluoropolymers: Poly(styrene)‐b‐poly(2, 3, 4, 5, 6‐pentafluorostyrene)‐b‐poly(2, 2, 3, 4, 4, 4‐hexafluorobutyl methacrylate) [PS‐b‐PFS‐b‐PHFBMA], a difluoroblock copolymer composed of PS‐b‐PHFBMA and a homopolymer composed of PHFBMA. Equilibrium and transport properties (e.g., ion exchange capacity, water uptake, water content, proton conductivity, and methanol permeability), were shown to be significantly influenced by the chemical nature of the fluoroblock copolymer, the fluoropolymer content, and their resulting morphology. Proton conductivity and methanol permeability were very sensitive to the incorporation of PHFBMA. Polymer blends composed of sulfonated poly(styrene‐b‐isobutylene‐b‐styrene) (SIBS SO3 H) and PHFBMA above 9 wt% showed interconnected ionic domains that have a shorter correlation length and high water content, which results in improved transport properties for direct methanol fuel cell (DMFC) applications. POLYM. ENG. SCI., 57:1262–1272, 2017. © 2017 Society of Plastics Engineers